2003
DOI: 10.1055/s-2003-43274
|View full text |Cite
|
Sign up to set email alerts
|

Time Limit and V·O2Slow Component at Intensities Corresponding to V·O2max in Swimmers

Abstract: The purpose of this study was to measure, in swimming pool conditions and with high level swimmers, the time to exhaustion at the minimum velocity that elicits maximal oxygen consumption (TLim at vVO(2)max), and the corresponding VO(2) slow component (O(2)SC). The vVO(2)max was determined through an intermittent incremental test (n = 15). Forty-eight hours later, TLim was assessed using an all-out swim at vVO(2)max until exhaustion. VO(2) was measured through direct oximetry and the swimming velocity was contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
25
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 26 publications
11
25
2
2
Order By: Relevance
“…The mean values obtained at the end of the incremental protocol are in accordance with those presented for middle distance swimmers [5, 6], but lower than those described for elite swimmers [811], runners [32, 33], cyclists [34, 35], and rowers [36, 37], probably explained by the use of a larger muscle mass in these sports. Also, the observed [La − ] max⁡ mean values are lower compared to other exercise modes, which can explain the lower R mean values found.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The mean values obtained at the end of the incremental protocol are in accordance with those presented for middle distance swimmers [5, 6], but lower than those described for elite swimmers [811], runners [32, 33], cyclists [34, 35], and rowers [36, 37], probably explained by the use of a larger muscle mass in these sports. Also, the observed [La − ] max⁡ mean values are lower compared to other exercise modes, which can explain the lower R mean values found.…”
Section: Discussionsupporting
confidence: 84%
“…Collectively, these studies seem to evidence that time sustained at intensities around vVO 2max⁡ depends also on the conditions in which they occurred. In fact, it has been reported that swimming flume might influence the VO 2max⁡ , vVO 2max⁡ , and the Tlim-vVO 2max⁡ assessment, as well as the swimming technique, and, therefore, could explain the differences found [8]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations